The Effect of Chemical Structure of OEG Ligand Shells with Quaternary Ammonium Moiety on the Colloidal Stabilization, Cellular Uptake and Photothermal Stability of Gold Nanorods - Salajkova, Sarka; Havel, Filip; Sramek, Michal; Novotny, Filip; Malinak, David; Dolezal, Rafael; Prchal, Lukas; Benkova, Marketa; Soukup, Ondrej; Musilek, Kamil; Kuca, Kamil; Bartek, Jiri; et al. (International journal of nanomedicine, 2021)
PURPOSE: Plasmonic photothermal cancer therapy by gold nanorods (GNRs) emerges as a promising tool for cancer treatment. The goal of this study was to design cationic oligoethylene glycol (OEG) compounds varying in hydrophobicity and molecular electrostatic potential as ligand shells of GNRs. Three series of ligands with different length of OEG chain (ethylene glycol units = 3, 4, 5) and variants of quaternary ammonium salts (QAS) as terminal functional group were synthesized and compared to a prototypical quaternary ammonium ligand with alkyl chain - (16-mercaptohexadecyl)trimethylammonium bromide (MTAB). METHODS: Step-by-step research approach starting with the preparation of compounds characterized by NMR and HRMS spectra, GNRs ligand exchange evaluation through characterization of cytotoxicity and GNRs cellular uptake was used. A method quantifying the reshaping of GNRs was applied to determine the effect of ligand structure on the heat transport from GNRs under fs-laser irradiation. RESULTS: Fourteen out of 18 synthesized OEG compounds successfully stabilized GNRs in the water. The colloidal stability of prepared GNRs in the cell culture medium decreased with the number of OEG units. In contrast, the cellular uptake of OEG+GNRs by HeLa cells increased with the length of OEG chain while the structure of the QAS group showed a minor role. Compared to MTAB, more hydrophilic OEG compounds exhibited nearly two order of magnitude lower cytotoxicity in free state and provided efficient cellular uptake of GNRs close to the level of MTAB. Regarding photothermal properties, OEG compounds evoked the photothermal reshaping of GNRs at lower peak fluence (14.8 mJ/cm2) of femtosecond laser irradiation than the alkanethiol MTAB. CONCLUSION: OEG+GNRs appear to be optimal for clinical applications with systemic administration of NPs not-requiring irradiation at high laser intensity such as drug delivery and photothermal therapy inducing apoptosis.
Keywords: zlato; nanotrubičky; Hydrophobic and Hydrophilic Interactions; Temperature; biologický transport; Ligands; ligandy; Biological Transport; oligoethylene glycol; Humans; photothermal stability; cellular uptake; gold nanorods; teplota; koloidy; lidé; quaternary ammonium salts; Quaternary Ammonium Compounds; Drug Stability; HeLa buňky; stabilita léku; Polyethylene Glycols; Nanotubes; hydrofobní a hydrofilní interakce; polyethylenglykoly; kvartérní amoniové sloučeniny; HeLa Cells; Colloids; Gold